2018
DOI: 10.1371/journal.pntd.0006276
|View full text |Cite
|
Sign up to set email alerts
|

The impact of passive case detection on the transmission dynamics of gambiense Human African Trypanosomiasis

Abstract: Gambiense Human African Trypanosomiasis (HAT), or sleeping sickness, is a vector-borne disease affecting largely rural populations in Western and Central Africa. The main method for detecting and treating cases of gambiense HAT are active screening through mobile teams and passive detection through self-referral of patients to dedicated treatment centres or hospitals. Strategies based on active case finding and treatment have drastically reduced the global incidence of the disease over recent decades. However,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…Subsequently, a large portion of the literature is concerned with how best to deploy existing tools in support of elimination goals. In this respect, a lot of attention was assigned to screening approaches [43,44,[70][71][72][73][74][75][76][77] and exploring testing algorithms [50,55].…”
Section: Goal: Global Eliminationmentioning
confidence: 99%
“…Subsequently, a large portion of the literature is concerned with how best to deploy existing tools in support of elimination goals. In this respect, a lot of attention was assigned to screening approaches [43,44,[70][71][72][73][74][75][76][77] and exploring testing algorithms [50,55].…”
Section: Goal: Global Eliminationmentioning
confidence: 99%
“…The ability to access facilities where HAT can be rapidly diagnosed shortens the time between infection and treatment, reducing potential transmission opportunities. Indeed, modelling has suggested that there is great potential in improving rates of passive case detection [50].…”
Section: Passive Detectionmentioning
confidence: 99%
“…Granular explorations of how HAT diagnosis actually happens in a passive detection context have also been limited. Indeed, despite its contribution to disease control over the last several decades [16], there has been remarkably little research on passive case detection, in general [12]. This empirical gap is perhaps particularly surprising considering the role this approach is expected to play in achieving elimination of HAT in the coming decade.…”
Section: Introductionmentioning
confidence: 99%